8th International conference on cell & stem cell engineering (ICCE) - International conference on cell & stem cell engineering 2010 Dublin, Ireland); El Haj, Alicia; Bader, Dan.; SpringerLink (Online service). (Berlin, Heidelberg Springer, 2011)
This volume presents selected peer-reviewed papers of the 8th International Conference on Cell & Stem Cell Engineering (ICCM) 2010 in Dublin. The contributions are written by leading scientists in Cell and Stem Cell Engineering and the topics of the papers include: Computational Cell Mechanics Experimental techniques in Cell Mechanics Molecular and Cell Imaging Cell Matrix Interactions Mechanotransduction and cell mechanics Cell sensing Cell processing Artificial cells Stem cell niche Cell Networks
Electronic reproduction.
Keywords: Stem cells -- Congresses; Electronic books